Research Progress in Swirl Separation Technology Based on Supersonic Refrigeration Effect - Zeng Yupei; Luo Ercang (Zhileng xuebao)
Swirl separation technology based on the supersonic refrigeration effect is a new method to remove water, heavy hydrocarbons, and other impurities from natural gas. In this article, first, the typical structure of a supersonic swirl separator and Laval nozzle design are reviewed; thereafter, the condensation phase transition theories of one-component and two-component gases are summarized. Subsequently, the effects of inlet and outlet parameters and nozzle structure parameters on the condensation characteristics of supersonic flow are summarized; finally, new applications in the fields of natural gas liquefaction and acid gas removal are reviewed. Although many domestic and international scholars have conducted considerable research, some problems still remain, and future prospects for supersonic swirl separation technology have been proposed.